Revolutionary Poetics and Social Transformation in the Works of Percy Bysshe Shelley - Bhattarai, Rajendra (International Research Journal of MMC, 2025)
Percy Bysshe Shelley, a noted Romantic poet, integrates artistic innovation with revolutionary political vision by presenting poetry as an active force for social transformation. The major objective of this article is to examine how Percy Bysshe Shelley’s revolutionary poetics articulate social and political critique and promote ideals of social transformation through his major poetic works “Ode to the West Wind”, “The Mask of Anarchy”, “Prometheus Unbound”, “Queen Mab, England in 1819”, “Ozymandias”, “The Revolt of Islam”, and “Song to the Men of England”. This article employed an exploratory research design in which the poetic and essay excerpts were taken as primary data, whereas the secondary data were utilized through comprehensive reviews of books, and journal articles. The excerpts were analyzed thematically by focusing on poetry as an active force for social transformation. The findings reveal Shelley’s poetry as a revolutionary force that unites imagination with political commitment to inspire social change. Shelley’s works consistently emphasize the need for awakening, resistance, and moral renewal. They envision the overthrow of tyranny, critique social injustice, highlight the fragility of oppressive power, and advocate for the rights and dignity of the marginalized and working classes. Through his poetic vision, Shelley merges ethical concern with political consciousness, portraying literature as a catalyst for social transformation. Together, they affirm Shelley’s belief in poetry as a means to challenge oppression and imagine a just society. The study offers important academic implications by presenting an interdisciplinary reading of Shelley that links poetic form with political ideology and social change by viewing poetry as a vehicle of revolutionary thought and a critical tool for social critique in Romantic, political, and cultural studies.